Fundamentals of Patenting and Licensing for Scientists and Engineers - Ma, Matthew Y (World Scientific Publishing Company, 2015)
The book offers a practical guide for scientists and engineers on patenting and licensing, explaining how to protect inventions and commercialize technology. The second edition updates legal developments and adds real-world examples to connect research with industry.